Creative Leading Corporation / Farhana Aini Hailin...[et al.] - Hailin, Farhana Aini; Zakaria, Nor Amalina; Hassan, Nur Diana Murni; Mohd Annuar, Nur Fatinah; Naim, Nurul Hidayah (2015)
Umbrella is a primarily a device to keep people dry in rain and shade a person from the sun. Mostly, it can be seen that umbrella is used by women. In the market, there is abundance of designs, colours and functions that can be choose. The improvement in our design may lead umbrella to a better user friendly and easy to carry to anywhere. Basically, the new invention that we apply to our umbrella is that it can expand from the small size to a larger size just by clicking the button provided in the umbrella's handle. One of the reasons that we come out with this idea is that we notice most of the students carry their own umbrella to the class which the size of the umbrella usually is small and fit for 1 person only. By the time of raining, they cannot share the umbrella with their friends and we found out, the umbrella's owner also may get wet because of the small umbrella. Therefore, our group come with the idea of a helping-hand solution by having an expand umbrella. As we gather the information that is heeded, we eventually come out with some of the fantastic ideas that never had been explored by the other designers out there. Our new invention idea is that by having just 1 umbrella, you can share it with your friends. The canopy for our umbrella can be enlarged at 2 times. Basically, the size will be small that fit for 1 person. Then it can enlarged to the medium size that fit for 2 or persons, and again, the canopy can enlarged to the large size that will be fit for 4 or 5 persons. Other than that, this umbrella can also be a table umbrella. The umbrella's weight is not heavy although it has added the canopy enlargement which it is easy to be carried to everywhere.